Modified adaptive second order sliding mode control: Perturbed system response robustness. (January 2020) - Seyedtabaii, S.
Abstract: Sensitivity to parameters, which is negative for any system; for an aircraft is destructive. In this respect, an Adaptive Second-order Sliding Mode Control (AS-SMC) is proposed to manage the unknown time-varying aircraft parameter uncertainty and un-modeled coupling perturbations. The employed adaptivity relaxes the required knowledge of the perturbation bound, the suggested sliding surface improves the system stability and bypassing the SMC reaching phase enhances the performance robustness. The effectiveness of the scheme in providing low tolerance responses with respect to the basic controller is illustrated through extensive simulations. The response is more appreciated when the system operates in a high angle of attack/sideslip conditions.